Loading on a wind turbine high-speed shaft gearbox bearing: Ultrasonic field measurements and predictions from a multi-body simulation. (March 2023) - Clarke, B.P.; Nicholas, G.; Hart, E.; Long, H.; Dwyer-Joyce, R.S.
Abstract: Wind turbine gearbox failures, many of which result from load-driven rolling element bearing failures, account for long downtimes and high maintenance costs. Non-invasive, in-situ measurement of bearing roller loads using ultrasound facilitates better understanding of the load history and failure mechanisms these gearbox bearings experience. In this study, ultrasonic load measurements from an instrumented high-speed shaft bearing were compared against results from a static multibody simulation. Measurements taken under steady operating conditions were found to agree well with the model. After quantification of the error in ultrasonic measurements the model enabled identification of load outliers which were attributed to transient events. Over- and under-loading instances may act to promote a variety of failure mechanisms, leading to premature bearing failure. Highlights: Ultrasonic sensors successfully inferred wind turbine HSS bearing load from signals. Measurements agreed well with results from a model of the turbine drivetrain. Ultrasound accuracy was load dependent and ranged from ± 0.4–1.0 kN. Low and high load outliers were attributed to transient loading events. A slight shift in bearing loaded zone were observed through sensor load ratio.